A straightforward approach to enhance the textural, mechanical and biological properties of injectable calcium phosphate apatitic cements (CPCs): CPC/blood composites, a comprehensive study. (15th October 2017) - Mellier, Charlotte; Lefèvre, François-Xavier; Fayon, Franck; Montouillout, Valérie; Despas, Christelle; Le Ferrec, Myriam; Boukhechba, Florian; Walcarius, Alain; Janvier, Pascal; Dutilleul, Maeva; Gauthier, Olivier; Bouler, Jean-Michel; et al.
Graphical abstract: Abstract: Two commercial formulations of apatitic calcium phosphate cements (CPCs), Graftys® Quickset (QS) and Graftys® HBS (HBS), similar in composition but with different initial setting time (7 and 15 min, respectively), were combined to ovine whole blood. Surprisingly, although a very cohesive paste was obtained after a few minutes, the setting time of the HBS/blood composite dramatically delayed when compared to its QS analogue and the two blood-free references. Using solid state NMR, scanning electron microscopy and high frequency impedance measurements, it was shown that, in the particular case of the HBS/blood composite, formation of a reticulated and porous organic network occurred in the intergranular space, prior to the precipitation of apatite crystals driven by the cement setting process. The resulting microstructure conferred unique biological properties to this material upon implantation in bone defects, since its degradation rate after 4 and 12 weeks was more than twice that for the three other CPCs, with a significant replacement by newly formed bone. Statement of Significance: A major challenge in the design of bone graft substitutes is the development of injectable, cohesive, resorbable and self-setting calcium phosphate cement (CPC) that enables rapid cell invasion with initial mechanical properties as close as bone ones. Thus, we describe specific conditions in CPC-blood composites where the formation of a 3D clot-like network can interact with the precipitated apatite crystals formed during the cement setting process. The resulting microstructure appears more ductile at short-term and more sensitive to biological degradation which finally promotes new bone formation. This important and original paper reports the design and in-depth chemical and physical characterization of this groundbreaking technology.